“APPROACHES TO REDUCING ENVIRONMENTAL IMPACT THROUGH THE USE OF RECYCLED CONSTRUCTION MATERIALS” - Abobakirova Zebuniso Asrorovna; Bobofozilov Oybek (Western European Studies, 2025)
This article analyzes the environmental advantages of recycling construction materials and its role in reducing the negative impact on the natural environment. Based on issues such as the increasing amount of construction waste, depletion of natural resources, and the growth of the carbon footprint, the importance of recycling technologies is highlighted. The study reviews best practices for reusing concrete, metal, wood, and plastic waste, methods for improving energy efficiency, and mechanisms for integrating these processes into the concept of sustainable construction. The findings indicate that the use of recycled materials not only enhances economic efficiency but also reduces environmental pressure, contributing to the development of the green economy
Keywords: construction waste; recycling; environmental sustainability